The Effectiveness of International Criminal Justice in Confronting the Crime of Genocide: The Genocide Committed Against the Yazidis in Iraq as a Case Study - Al-Maliki, Hadi (Journal of Legal Sciences, 2026)
This research investigates a structural problem in the contemporary international criminal justice system by examining the systematic contradiction between the principle of individual criminal responsibility -- the cornerstone of international criminal law -- and the collective, organized nature of major international crimes, particularly genocide. The research hypothesis posits that the principle of individual responsibility, despite its philosophical and moral necessity to avoid collective punishment, creates a structural justice gap when applied to crimes committed by entire states or organizations against large human groups.Through a case study of the Yazidi genocide in Iraq (August 2014), the research demonstrates a dual deficiency in the international system: jurisdictional deficiency resulting from Iraq's non-adherence to the Rome Statute and the absence of Security Council referral, depriving the International Criminal Court of jurisdiction; and a deeper structural deficiency represented by the inadequacy of the individual accountability mechanism -- even when available -- to address collective crimes of the magnitude experienced by the Yazidis (approximately 5,000 killed, over 6,800 abducted, 200,000 displaced). Based on a critical analytical methodology combining legal positivism, philosophical analysis, and comparative historical method, the research concludes that the ontological contradiction between individual responsibility and collective criminal action undermines the effectiveness of the international penal system and frustrates the achievement of its two primary objectives: corrective justice (redress for victims) and general deterrence (prevention of crime repetition).